2020
DOI: 10.1371/journal.pone.0227339
|View full text |Cite
|
Sign up to set email alerts
|

Using electronic health record system triggers to target delivery of a patient-centered intervention to improve venous thromboembolism prevention for hospitalized patients: Is there a differential effect by race?

Abstract: BackgroundRacial disparities are common in healthcare. Venous thromboembolism (VTE) is a leading cause of preventable harm, and disparities observed in prevention practices. We examined the impact of a patient-centered VTE education bundle on the non-administration of preventive prophylaxis by race. MethodsA post-hoc, subset analysis (stratified by race) of a larger nonrandomized trial. Pre-post comparisons analysis were conducted on 16 inpatient units; study periods were October 2014 through March 2015 (basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Other studies have reached similar conclusions [31][32][33]. Though, many embedded VTE warning software has been developed and integrated with electronic medical record system but this software is mostly based on Caprini Risk Assessment Scale, or Padua Assessment Scale, etc [34][35][36][37]. Vyas et al [38] adopted the analysis way of Ishikawa Fishbone Diagram, and found that main reason for the improper prevention of DVT were the lacks of unified standard specifications, the computerized input system for doctors' orders and effective risk assessment methods [39].…”
Section: Clinical Status Of Early Warning Mechanism Of Venous Thrombomentioning
confidence: 67%
See 1 more Smart Citation
“…Other studies have reached similar conclusions [31][32][33]. Though, many embedded VTE warning software has been developed and integrated with electronic medical record system but this software is mostly based on Caprini Risk Assessment Scale, or Padua Assessment Scale, etc [34][35][36][37]. Vyas et al [38] adopted the analysis way of Ishikawa Fishbone Diagram, and found that main reason for the improper prevention of DVT were the lacks of unified standard specifications, the computerized input system for doctors' orders and effective risk assessment methods [39].…”
Section: Clinical Status Of Early Warning Mechanism Of Venous Thrombomentioning
confidence: 67%
“…The VTE prediction model are established with the purpose of making accurate assessment and diagnosis of VTE in the first time and avoiding adulterating human factors as much as possible. We know that there is a lot of VTE-related information in the electronic medical record system [27,[33][34][35][40][41][42], and this information needs to be further explored and fully utilized in the clinical warning of VTE. The VTE risk warning model makes full use of the Caprini risk assessment scale, which is widely used in clinical medicine and surgery, with the important clinical symptoms and signs of VTE patients and laboratory examination indicators, to carry out comprehensive and multidimensional comprehensive warning and achieve higher prediction efficiency.…”
Section: Clinical Significance Of Early Warning Model For Venous Thromentioning
confidence: 99%
“…Though, many embedded VTE warning software has been developed and integrated with electronic medical record system but such software was mostly based on Caprini Risk Assessment Scale, or Padua Assessment Scale, etc. [33][34][35][36]. Vyas et al [37] adopted the analysis way of Ishikawa Fishbone Diagram, and found that main reason for the improper prevention of DVT were the lacks of unified standard specifications, the computerized input system for doctors' orders and effective risk assessment methods [38].…”
Section: Clinical Status Of Vte Early Warning Mechanismmentioning
confidence: 99%
“…The VTE prediction model were established with purpose of making accurate assessment and diagnosis of VTE in the first time and avoiding adulterating human factors as much as possible. We know that there is a lot of VTE-related information in the electronic medical record system [27,[33][34][35][39][40][41], and such information needs to be further explored and fully utilized in the clinical VTE warning. The VTE risk warning model made full use of Caprini risk assessment scale, which was widely used in clinical medicine and surgery, with the important clinical symptoms and signs of VTE patients and laboratory examination indicators, to carry out comprehensive and multi-dimensional warning and achieve higher prediction efficiency.…”
Section: Clinical Significance Of Vte Early Warning Modelmentioning
confidence: 99%
“…10,15 For patient refusal of prophylaxis doses, 14 we conducted a second trial and found that a real-time, alert-triggered patient-centered education bundle significantly reduced any missed dose of VTE prophylaxis by 43% and patient refusal by 47%, 16 with no difference by race. 17…”
Section: Introductionmentioning
confidence: 99%